Extended spin coherence of the zinc-vacancy centers in ZnSe with fast optical access - Erik Kirstein (Nature Portfolio, 2021)
Ideal qubits should exhibit, simultaneously, long spin coherence times and fast initialization. Here, defect centers in ZnSe epilayers, introduced by ex-situ fluorine implantation, are displaying spin coherence times of 100 ns at room temperature and fast optical access on the picosecond timescale.